Advances in data and web management : Joint International Conferences, APWeb/WAIM 2009 Suzhou, China, April 2-4, 2009 proceedings (Lecture notes in computer science / editors Gerhard Goos, Juris Hartmanis, and Jan van Leeuwen ;, 2009)
This book constitutes the proceedings of the joint International Conference APWeb/WAIM 2009 which was held in Suzhou, China, during April 1-4, 2009. The 42 full papers presented together with 26 short papers and the abstracts of 2 keynote speeches were carefully reviewed and selected for inclusion in the book. The topics covered are query processing, topic-based techniques, Web data processing, multidimensional data analysis, stream data processing, data mining and its applications, and data management support to advanced applications.